(untitled) (Informatica, 2025)
This research investigates the complexities of engineering measurement, positioning, and layout systems through a comprehensive nonlinear analysis simulation. The study thoroughly analyzes and compares the positioning accuracy between satellite navigation systems and GPS combinations, utilizing actuarial data derived from the Global Positioning System (GPS). The methodology involves the precise measurement and labeling of four C-level satellite control points (C1, C2, C3, and C4) and seven third-class benchmarks (S1 to S7) within the project vicinity using experimental analysis. The distribution and integrity of the control points and benchmarks were consistently maintained. The experimental results highlight the practical benefits of integrating satellite navigation systems with GPS in engineering surveying. The multi-system positioning approach significantly improves positioning accuracy and enhances the reliability of measurement data. These findings underscore the effectiveness of this approach in engineering surveys and demonstrate its potential to elevate the precision of future positioning surveys.